Analysis of inequities between demographic and social determinants associated with overweight and obesity - Pabyle Alves Flauzino; Ilana Nogueira Bezerra; Julia Sichieri Moura; Rosely Sichieri (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: To assess demographic and social determinants associated with the prevalence of overweight and obesity from a population survey. Methods: Cross-sectional study with 28,153 adults participating in the 2017-2018 Household Budget Survey. Self-reported weight and height were used to estimate the prevalence of overweight and obesity, in addition to information on sociodemographic characteristics such as age (continuous), sex (male/female), skin color or race (white, brown, and black), location of residence (urban or rural), and per capita family income (quartile). Linear regression models were used to assess changes in mean BMI according to age and income in each area (urban/rural), stratified by sex and race/skin color. Results: In men, overweight and obesity were more prevalent in urban than rural areas, but there was no such difference in women. Income was quadratically related to the mean BMI among women, while in men the prevalence increased with income. In women, higher income was associated with lower BMI, except for black women, who did not show variation with income and were the ones with the highest prevalence of obesity. Men in rural areas had a much lower BMI and, respectively, a lower prevalence of obesity. Conclusion: We found no difference between extreme groups of possible inequality with regard to overweight and obesity. However, the prevalence of grade I obesity in men was different according to the area, being higher in men living in urban areas; and the highest prevalence of obesity according to race/color occurred among black women in the highest income quartile.